Perancangan Sistem Simpan Pinjam Berbasis Website - Eka Putra; Rian Farta Wijaya; Robi Krisna (STMIK Budi Darma, 2022)
Cooperatives as a form of organization that is important in increasing economic growth. Savings and loans cooperatives are one of the alternatives for members to get funds in an effort to improve the standard of living, meet daily needs and develop a business. In addition, savings and loan cooperatives are also one of the options for investing funds (saving). People like to save in savings and loan cooperatives because in addition to the accused, they also get year-end interest or can also get residual business proceeds. At the Office of Cooperatives and SMEs in Medan Helvetia District, the process of processing savings and loans data is currently still doing manual methods. This kind of data processing can cause insecure data in storage. Therefore, the research will create a data processing system with sufficient computerization. So that the report that will be needed can later be processed appropriately by the Office of Cooperatives and SMEs of Medan Helvetia District. From the problems that have been obtained so that a solution can be obtained from its handling by implementing a web-based savings and loans application, hopefully this application can help the Medan Helvetia District Cooperatives and SMEs Office in handling the problem of processing savings and loan reports so that it does not take time.